Law enforcement towards the management of the forestry mangrove Province South Sulawesi - Prof Syahruddin Nawi; Hikmawati Mustamin; Ilham Abbas; Sultang Sultang (Indonesia Prime, 2018)
This research aims to find out Nature of law enforcement In Physical Education Mangrove forests in southern Sulawesi. In addition to identifying and analyzing the factors influencing law enforcement efforts in the conservation of mangrove forests in southern Sulawesi and in finding a strategy or enforcement of a new model law while preserving Mangrove forests in southern Sulawesi. The results showed that the first, espionage and legal compliance against a regulatory and forestry legal environment are being perfected together in an attempt to actively enforce the law that is ravaged, preventively and oppressive in efforts to conserve mangrove forests in the South Sulawesi. The level of support and legal compliance against the rule of law is at a high level of four category categories (Low, medium, high and very Tinggi). This indicates that the people of De Sulawesi are obedient and obey related laws against purveying mangrove forests. Secondly, Factors that constrain law enforcement efforts in the communities existance from the negative behavior of law enforcement officials who became disoriented against those who harmed the harm of mangrove plant persons. However Therefore Of Behind it, a supporting factor in an effort to enforce Community law is to recognize the community that supports law enforcement to be a moral commitment "to protect the Aboriginal community with identically protecting oneself and third, A strategy and model to be undertaken in the preservation efforts of mangrove forests in southern Sulawesi to make it integrated, namely in the form of Aquaculture (farmed) sebaiknAlready Make Behind a fangy (Matern); All parties should encourage the creation of a caring culture with mangrove forest ecosystems (mangrove); Mangrove damage (mangrove) rehabilitation should be done through replanting of mangroves. Mangrove planting should involve the community. His model can Form of part played by Community in the eggplant, planting and maintenance as well as conservation-based use of mangrove forests; Spatial reconstruction of the coastal area, in the form The settlement And Vegetation InIlayah Beach can be organized as an ecological citys At the same time can be used as waterfront tours (ecotourism) in the form of nature tourism or any other form; To increase public awareness and motivation to maintain and use the mangroves responsibly; ThezIn Business and others-OtherIt should address the conservation aspect; Increased knowledge and use of coal wisdomkAl for conservation; Federal Forest Conservation Communications Programme, and law enforcement An integrated approach